The role of finger kinematics in the acquisition of number meaning in kindergarten: a pilot study - Bidet-Ildei, Christel; Vilain, Capucine; Fevin, Sabine; Francisco, Victor; Vibert, Nicolas (Frontiers in Education, 2024)
In the framework of the acquisition of number meaning in young children, we present here an original methodology based on the observation of point-light display to develop the capacity to associate non-symbolic and symbolic representations of numbers. The main result of this paper is to demonstrate for the first time that point-light displays representing counting can foster the acquisition of number meaning in young children suggesting that kinematics may be crucial to the development of number processing. Even though future research is needed to confirm and specify this effect, this potentially opens up new and interesting perspectives for remediation in children who have specific difficulty acquiring number meaning.